2013
DOI: 10.1007/s00221-013-3749-0
|View full text |Cite
|
Sign up to set email alerts
|

In vivo microdialysis of glutamate in ventroposterolateral nucleus of thalamus following electrolytic lesion of spinothalamic tract in rats

Abstract: Central pain is one of the most important complications after spinal cord injury (SCI), and thereby, its treatment raises many challenges. After SCI, in a cascade of molecular events, a marked increase in glutamate at the injury site results in secondary changes which may impact on supraspinal regions, mainly ventroposterolateral (VPL). There is little information about the changes in glutamate metabolism in the VPL and whether it contributes to SCI-related central pain. The present study was performed to eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
8
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 38 publications
2
8
0
Order By: Relevance
“…These results are also consistent with the increased hyperexcitability in the brain that is only evident after a painful facet joint injury (Fig. 2) since prolonged exposure to glutamate is correlated with increased neuronal hyperexcitability [59,60]. …”
Section: Discussionsupporting
confidence: 81%
“…These results are also consistent with the increased hyperexcitability in the brain that is only evident after a painful facet joint injury (Fig. 2) since prolonged exposure to glutamate is correlated with increased neuronal hyperexcitability [59,60]. …”
Section: Discussionsupporting
confidence: 81%
“…An accumulating body of evidence suggests that glutamate plays a role in the transduction of sensory input at the periphery and participates in the central sensitization that is associated with the development of pathological pain (Osikowicz et al, 2013). In animal models of pathological pain, increased glutamate release or transmission is observed in injured tissues, DRG, spinal cord, and different supraspinal regions, such as the anterior cingulate cortex (ACC), periaqueductal gray (PAG), and ventroposterolateral nucleus (VPL; Omote et al, 1998;Somers and Clemente, 2002;Wen et al, 2003;Xu et al, 2008;Inquimbert et al, 2012;Ho et al, 2013;Yan et al, 2013;Ghanbari et al, 2014;Gong et al, 2014;, and the drugs acting against glutamate release attenuate the painrelated behaviors induced in animal models (Bleakman et al, 2006;Kumar et al, 2010aKumar et al, , 2013Naderi et al, 2014). In contrast, intraplantar, intrathecal, or lateral ventricle injection of glutamate exhibits an algesic effect (Beirith et al, 1998;Shi et al, 2010;Osgood et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies indicate that glutamate plays an important role in the transduction of sensory input at the periphery and is critically involved in central sensitization, which is associated with chronic pain. Glutamate regulates nociceptive processes at different levels of the nervous system, including dorsal root ganglion (DRG), spinal cord, and different supraspinal regions (Omote et al, ; Somers and Clemente, ; Wen et al, ; Xu et al, ; Inquimbert et al, ; Ho et al, ; Osikowicz et al, ; Yan et al, ; Ghanbari et al, ; Gong et al, ; Li et al, ). However, the roles of glutamate and different types of glutamate receptors in the RN in the development of neuropathic pain are currently unknown.…”
mentioning
confidence: 99%
“…Among the main supraspinal projections, the spinothalamic tract is the most prominent ascending nociceptive pathway in the spinal cord and projects into the ventral posterior lateral (VPL) and ventral posterior medial (VPM) nucleus involved with discriminative components of pain sensitivity and nonspeciic thalamic nucleus (centromedial, centrolateral, laterocentral and intralaminar), related to the affective component of pain GHANBARI et al, 2014).…”
Section: Cortical Stimulation and Neuropathic Painmentioning
confidence: 99%
“…On the basis of functional criteria, the main cortical regions involved in pain response are the motor cortex, primary (S-I) and secondary (S-II) sensory cortex (SCHNITZLER;PLONER, 2000;GUSTIN et al, 2012). However, it has been observed that patients with speciic brain lesions, particularly in the SI cortex, are still able to feel pain (BROOKS; TRACEY, 2005), and an intense activity has been seen in the SI cortex of patients with chronic neuropathic pain compared to patients with chronic non-neuropathic pain (GUSTIN et al, 2012).…”
Section: Cortical Stimulation and Neuropathic Painmentioning
confidence: 99%